2014
DOI: 10.1186/1471-213x-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of the laminin β LN domain and collagen IV during cardiac extracellular matrix formation and stabilization of alary muscle attachments revealed by EMS mutagenesis in Drosophila

Abstract: BackgroundThe Drosophila heart (dorsal vessel) is a relatively simple tubular organ that serves as a model for several aspects of cardiogenesis. Cardiac morphogenesis, proper heart function and stability require structural components whose identity and ways of assembly are only partially understood. Structural components are also needed to connect the myocardial tube with neighboring cells such as pericardial cells and specialized muscle fibers, the so-called alary muscles.ResultsUsing an EMS mutagenesis scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 103 publications
(150 reference statements)
1
63
0
Order By: Relevance
“…A forward genetic screen of Drosophila led to identification of hypomorphic point-specific mutations in the b1-LN domain that cause prominent defects in cardiac basement membrane generation and cardiac morphogenesis (Hollfelder, Frasch, & Reim, 2014). The distribution of defective laminin in the basement membranes around the myocardial tube lacked continuity and instead appeared as a series of disconnected dots.…”
Section: Figurementioning
confidence: 99%
“…A forward genetic screen of Drosophila led to identification of hypomorphic point-specific mutations in the b1-LN domain that cause prominent defects in cardiac basement membrane generation and cardiac morphogenesis (Hollfelder, Frasch, & Reim, 2014). The distribution of defective laminin in the basement membranes around the myocardial tube lacked continuity and instead appeared as a series of disconnected dots.…”
Section: Figurementioning
confidence: 99%
“…4E-E″). Muscle PC into FC divisions do not occur in Regulator of cyclin A1 (Rca1) mutant embryos, and Rca1 mutations were obtained in an EMS screen utilizing org-1-RFP as a marker for abnormal development of AMs [and LO1/VT1/SBM muscles (Hollfelder et al, 2014)]. Triple staining of Rca1 embryos showed that, in the absence of division, the AM PC remains Org-1 positive and Zfh1 negative (Fig.…”
Section: Am and Tarm Lineage Analysesmentioning
confidence: 99%
“…Projections and three-dimensional reconstructions were created using ImageJ (NIH) and Volocity (PerkinElmer) software, respectively. Time-lapse imaging of embryos carrying GFP and RFP reporter genes was performed as previously described (Hollfelder et al, 2014).…”
Section: Immunohistochemistry and Time-lapse Imaging Of Gfp/rfp Repormentioning
confidence: 99%
“…To determine whether org-1 is also involved in the establishment of the adult AMs, we probed larvae, pupae, and adults for Org-1 protein expression as well as for the reporters org-1-HN18-RFP (org-1-RFP) and org-1-HN39-nGFP (org-1-nGFP), which recapitulate somatic muscle expression of org-1 in the embryo [13,14]. We detected Org-1 expression and enhancer activity only in anterior AMs of wandering third instar larva and in early pupal stages ( Figures 1A and 1A 0 ).…”
Section: Resultsmentioning
confidence: 99%